2009
DOI: 10.1073/pnas.0911281106
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid seeds formed by cellular uptake, concentration, and aggregation of the amyloid-beta peptide

Abstract: One of the neuropathological hallmarks of Alzheimer's disease (AD) is the amyloid plaque, primarily composed of aggregated amyloidbeta (A␤) peptide. In vitro, A␤1-42, the major alloform of A␤ found in plaques, self-assembles into fibrils at micromolar concentrations and acidic pH. Such conditions do not exist in the extracellular fluid of the brain where the pH is neutral and A␤ concentrations are in the nanomolar range. Here, we show that extracellular soluble A␤ (sA␤) at concentrations as low as 1 nM was tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
385
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 379 publications
(427 citation statements)
references
References 45 publications
(47 reference statements)
38
385
1
3
Order By: Relevance
“…This is supported by some recent reports demonstrating that A␤ in culture medium is internalized and aggregated intracellularly into fibrils, eventually causing membrane disruption (47,48). Further studies are required to dissect the structural and molecular mechanisms underlying the critical role of protofibril-monomer interactions in A␤ toxicity.…”
Section: Discussionmentioning
confidence: 63%
“…This is supported by some recent reports demonstrating that A␤ in culture medium is internalized and aggregated intracellularly into fibrils, eventually causing membrane disruption (47,48). Further studies are required to dissect the structural and molecular mechanisms underlying the critical role of protofibril-monomer interactions in A␤ toxicity.…”
Section: Discussionmentioning
confidence: 63%
“…It has been shown that the specific chemical microenvironments of cellular compartments, such as endosomes, can enhance protein aggregation by several orders of magnitude (41). Our study presents a physicochemical rationale for such effects in the case of the aggregation of α-synuclein.…”
Section: Discussionmentioning
confidence: 97%
“…The internalization of soluble amyloidogenic species has been described previously in cell culture for ␣-synuclein (15,28) and both in cell culture and in vivo for A␤ (14,24) either by specific uptake through receptor-mediated endocytosis or passive diffusion across the cell membrane. In the case of A␤, the internalization of soluble species has been demonstrated to promote maturation into larger aggregates due to the acidic pH and increased concentration generated in the lysosomes.…”
Section: Discussionmentioning
confidence: 99%